Identification of Electrical Discharge on Electric Insulation Material Using Acoustic Emission Method - J M Nainggolan; I Garniwa M K; A Raharjo (IAES Indonesia Section, 2016)
Insulation system is essential to be equipped on high voltage equipment. One of the tests on insulation system is the electrical discharge test. In this work, the electrical discharge detected using an acoustic emission method to find out the characteristic of the discharge. Epoxy resin was taken as the insulation material, whereas one to two artificial holes were made inside the insulation. An AE sensor placed at a distance of 24 mm and 36 mm away from holes or discharge source. The main frequency component of the detected AE signal on single hole test was approximately 975 kHz. Meanwhile, test on double holes caused two main frequency component; i.e. 63 kHz and 930 Khz. For single hole test and sensor distance of 36 m, the AE signal intensity tends to be worth 40% from the AE signal at a distance of 24 mm.